Applying Peter Palchinsky’s Three Industrial Design to Improve Performance of Government Venture Capitals in Malaysia - Mohd Suhaimi Mohamed Ariffin; Haslinah Muhammad; Mazlan Hassan; Abdul Rahim Abdul Samad (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Purpose: On the background of substantial decline in foreign direct investment (FDI) flow into Malaysia, the GVCs are suggested to apply the Palchinsky principles to raise performances hence contributing to the socioeconomic growth of Malaysia. Research Methodology: By conceptually integrating the Peter Palchinsky’s three industrial design with literature on innovation. Results: First, GVCs to adopt collective criteria chosen by the technopreneurs when evaluating funds applications. Second, to let them choose among themselves who should get the funding in a given cycle instead of decided by the management of GVCs alone. Third, adopt lottery like selection to choose winners eligible for funding. Fourth, shared responsibility among technopreneurs is another possible method where applicants are organized in a group and funding given to a ‘deserving’ group rather than to an individual technology-based company. Lastly, performance bonuses to deserving personnel at GVCs. Limitations: The absence of data built upon the suggestions made in the study, limits the ability to measure potential impact. Singling out punctuated cases of success does not offer direct evidence that learning from failures could actually improve innovation. Contribution: Innovation in venture capital activities and add volume to the of entrepreneurial finance literature.